Five new species of Jaspis (Porifera: Demospongiae: Tetractinellida:Astrophorina) from Brazil with redescription of the type species Jaspis johnstonii (Schmidt, 1862) - Lira, Juliana; Pinheiro, Ulisses (Zootaxa, 2015)
The genus Jaspis comprises 32 valid species, six of which were previously recorded from the Atlantic Ocean. Two species have already been recorded from the Brazilian coast: J. johnstonii and J. salvadori (Rio Grande do Sul and Espírito Santo States respectively). Their respective type specimens, deposited at Muséum National d’Historie Naturelle, Paris (Jaspis salvadori, holotype) and at Universalmuseum Joanneum, Zoology Center of Natural History, Austria (Jaspis johnstonii, syntype) were reexamined, but due to differences in spicule composition these records are considered to be invalid. The present paper describes five new species of Jaspis collected on the Brazilian coast (Jaspis atolensis sp. nov., J. iacuitaster sp. nov., J. corticomicroxea sp. nov., J. variaster sp. nov. and J. gigoxea sp. nov.) bringing the total number of species worldwide to 36, all of which were compared in tabular format. The type species, Jaspis johnstonii, was also redescribed.